2010
DOI: 10.1016/s1684-1182(10)60047-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Third-generation Cephalosporin Resistance on Adult In-hospital Mortality From Post-neurosurgical Bacterial Meningitis

Abstract: These findings may portend the spread of serious resistance to third-generation cephalosporins in nosocomial Gram-negative bacilli throughout the neurosurgical units, suggestive of the need to reassess the empirical use of third-generation cephalosporins in post-neurosurgical bacterial meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
2
20
0
2
Order By: Relevance
“…Third-generation cephalosporin-resistant strains have become increasingly common in our study, which was also found in recent studies [43][44][45]. The resistance of Ab and KP to ceftriaxone/ceftazidime was 90.0%/87.1% and 75.7%/61.8%, which is in accordance with the other studies [35,46].…”
Section: Discussionsupporting
confidence: 92%
“…Third-generation cephalosporin-resistant strains have become increasingly common in our study, which was also found in recent studies [43][44][45]. The resistance of Ab and KP to ceftriaxone/ceftazidime was 90.0%/87.1% and 75.7%/61.8%, which is in accordance with the other studies [35,46].…”
Section: Discussionsupporting
confidence: 92%
“…Intermediate and resistant isolates were considered non-susceptible [11]. Multi-drugs resistant (MDR) GNB was used to describe isolates that were non-susceptible to all antibiotics routinely tested including amikacin, (ampicillin-sulbactam in A. baumannii ), ceftriaxone, ceftazidime, cefepime, ciprofloxacin, imepenem, and meropenem [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Another important therapeutic consideration in antibiotic use is the emergence of multi-drug resistant bacterial strains in G(-) ABM [11-13,20-25]. This problem is notable especially in patients with underlying G(-) ABM and a super-infection caused by another G(-) pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…"Relapse" of meningitis was considered if it was also caused by S. marcescens within 3 weeks of the completion of therapy for the initial episode. 16,20 Descriptive epidemiology Data collected from the enrolled patients included demographics, comorbid illnesses, clinical presentations and diagnoses, neurosurgeries in recent 3 months, laboratory data, severity of illness [Glasgow Coma Scale (GCS) score and Sequential Organ Failure Assessment (SOFA) score], 21 treatment courses and outcomes. Comorbid illnesses included diabetes mellitus, hepatic dysfunction (defined as the serum total bilirubin level !2.0 mg/dL or liver cirrhosis), renal insufficiency (defined as a serum creatinine level !2.0 mg/dL or a requirement of hemodialysis), chronic lung diseases, heart failure, and hematologic or solid organ malignancies.…”
Section: Study Design Patients and Case Definitionmentioning
confidence: 99%
“…16 However, the literature concerning the risk factors, impacts of antimicrobial therapy and clinical outcomes for S. marcescens meningitis were limited. Hence, we conducted this retrospective study to investigate the epidemiology, prognostic factors, and treatment outcomes of S. marcescens meningitis.…”
Section: Introductionmentioning
confidence: 99%